Structural Change and the Kaldor Facts of Economic Growth - Reto Foellmi; Josef Zweimüller (Institute for the Study of Labor (IZA), 2002)
We present a model in which two of the most important features of the long-run growth process are reconciled: the massive changes in the structure of production and employment; and the Kaldor facts of economic growth. We assume that households expand their consumption along a hierarchy of needs and firms introduce continuously new products. In equilibrium industries with an expanding and those with a declining employment share coexist, and each such industry goes (or has already gone) through a cycle of take-off, maturity, and stagnation. Nonetheless macroeconomic aggregates grow pari passu at a constant rate.
Keywords: L16; O31; O11; O40; D91; 330; Kaldor facts; balanced growth; structural change; innovation; hierarchic preferences; demand externalities; multiple equilibria; Gleichgewichtiges Wachstum; Strukturwandel; Theorie